Thyrotropin serum levels and coexistence with Hashimoto's thyroiditis as predictors of malignancy in children with thyroid nodules - Giuseppina Zirilli; Giuseppina Salzano; Domenico Corica; Giovanni Battista Pajno; Cristina Mignosa; Giorgia Pepe; Filippo De Luca; Giuseppe Crisafulli (BMC, 2019)
Abstract Thyroid cancer (TC) in childhood is a rare disease characterized by an excellent prognosis. Thyroid nodules in children, although less common than in adults, have a greater risk of malignancies, particularly in those cases associated with anamnestic, clinical and ultrasonographic risk factors. Among the factors, which have been found to be linked with an increased relative risk of TC in children, an important role seems to be possibly played by an underlying nodular Hashimoto's thyroiditis (HT) and by the serum levels of TSH. Aim of this Commentary was to specifically address this last point. According to the available pediatric literature on the relationships between these risk factors and phenotypical expression of TC in children, it is possible to conclude that: 1) It is not completely clarified if HT per se predisposes to malignancy or if it represents an incidental histologic finding in cases with TC or if it may be the result of an immune response against tumoral cells. 2) It is unclear whether phenotypic expression of TC is more severe in the cases with associated HT but normal TSH serum levels. 3) Persistently elevated TSH levels play an independent role as predictors of the likelihood of TC, especially in children but also in adults. 4) Patients with nodular HT and subclinical hypothyroidism need to be treated with Levothyroxine in order to prevent the development of both TC and severe thyroid dysfunctions.